Silicon odometer : an on-chip reliability monitor for measuring frequency degradation of digital circuits - Kim, Tony Tae-Hyoung (2010)
Precise measurement of digital circuit degradation is a key aspect of aging tolerant digital circuit design. In this study, we present a fully digital on-chip reliability monitor for high-resolution frequency degradation measurements of digital circuits. The proposed technique measures the beat frequency of two ring oscillators, one stressed and the other unstressed, to achieve 50 X higher delay sensing resolution than that of prior techniques. The differential frequency measurement technique also eliminates the effect of common-mode environmental variation such as temperature drifts between each sampling points. A 265 X 132 mum square test chip implementing this design has been fabricated in a 1.2 V, 130 nm CMOS technology. The measured resolution of the proposed monitoring circuit was 0.02%, as the ring oscillator in this design has a period of 4 ns; this translates to a temporal resolution of 0.8 ps. The 2 mus measurement time was sufficiently short to suppress the unwanted recovery effect from concealing the actual circuit degradation.